Inclusive bilingual early years education by means of the Reggio Emilia Approach - Marton, Vera; Kovács, Ivett Judit; Czachesz, Erzsébet (Gyermeknevelés Tudományos Folyóirat, 2022)
In diverse classrooms, bilingual early years education demands an inclusive approach for effective language acquisition. In the Reggio Emilia Approach, all children are viewed to be genuine and unique with individual ways and special rights. This paper aims to identify the aspects of the Reggio Emilia Approach that supports inclusive education. The research was conducted in a mixed-age group within a bilingual setting located in Budapest. Different qualitative research methods were used as data sources, including document analysis, participant observation, and unstructured interviews. The data analysis revealed a broader concept of inclusion in the setting. Through the project- based and experience-based learning fostered by an emergent curriculum, children can discover the world at their own pace. Children can work in micro and macro groups on meaning-making and understanding in activities tailored to their individual needs. The teachers scaffold their learning as facilitators supporting independence, cooperation, and peer-assistance while emphasising community-based learning. In the Reggio Emilia Approach, diversity is celebrated, and each child can be connected to differently. By filling the environment with variables, teachers allow for the inclusion of all children into activities, problems, and thinking.